2009
DOI: 10.1159/000219680
|View full text |Cite
|
Sign up to set email alerts
|

Full-Field Electroretinography Obtained Using a Contact Lens Electrode with Built-In High-Intensity White-Light-Emitting Diodes Can Be Utilized in Toxicological Assessments in Rats

Abstract: Full-field electroretinography (ERG) using contact lenses with built-in LED was performed on albino rats, and used to evaluate the visual toxicity of sodium iodate (NaIO3). Experiment 1 was carried out to determine the optimal conditions in rats relating to stimulus intensity, background illumination, and light adaptation period. As a result, we found that a full-field ERG was recorded under the following conditions: stimulus intensity: –3.5 log cd s/m2 in rod response; background intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
3
4
0
Order By: Relevance
“…Our assumption may be confirmed by the relatively stable b-wave detected in the photopic single-flash cone response on the 1st day after the injection of the higher dose of NaIO 3 , elicited under the rod suppression conditions. The observation is consistent with a recently published report indicating that the retinal toxicity induced by a very high dose (50 mg/kg) of NaIO 3 was expressed primarily in rods, followed by cones [22]. Nevertheless, the complete RPE disintegration and subsequent acute photoreceptor degeneration observed on the 3rd day after exposure to our high concentration of NaIO 3 resulted in total suppression of both scotopic and photopic retinal function.…”
Section: Discussionsupporting
confidence: 92%
“…Our assumption may be confirmed by the relatively stable b-wave detected in the photopic single-flash cone response on the 1st day after the injection of the higher dose of NaIO 3 , elicited under the rod suppression conditions. The observation is consistent with a recently published report indicating that the retinal toxicity induced by a very high dose (50 mg/kg) of NaIO 3 was expressed primarily in rods, followed by cones [22]. Nevertheless, the complete RPE disintegration and subsequent acute photoreceptor degeneration observed on the 3rd day after exposure to our high concentration of NaIO 3 resulted in total suppression of both scotopic and photopic retinal function.…”
Section: Discussionsupporting
confidence: 92%
“…Our ERG setup yielded response profiles corresponding to those obtained with commercial ERG setups and those previously described in rats by Yamashita et al (2009), who utilized the same contact electrodes. A typical normal ERG response is shown in figure 1(a).…”
Section: Ergsupporting
confidence: 54%
“…This type of electrode has been used in humans (Suzuki et al 1998, Tsuruoka et al 2004, dogs (Kim et al 2008, Yu et al 2007, Sasaki et al 2006, Maehara et al 2005, quail (Endo et al 2008) and rabbits (Maia et al 2004). There are four reports in the literature that describe its use in rats, but with a different ERG setup (Goto et al 2002, Grozdanic et al 2003, Yoneda et al 2003, Yamashita et al 2009.…”
Section: Introductionmentioning
confidence: 99%
“…One of them, sodium iodate (NaIO 3 ), is a stable retinotoxin that has been used as a RD animal model [17, 24]. However, two other study groups demonstrated a mismatch between visual function and histopathology of the retina [25, 26]. Additionally, in our preliminary test, NaIO 3 was not likely to reduce ERG responses significantly and or show apparent histopathologic findings (data not shown).…”
Section: Discussionmentioning
confidence: 79%